Comprehensive microarray analysis for the identification of therapeutic targets within HIF-1α signalling networks in diet-induced obesity via hypothalamic inflammation - Hai Guo; Lijuan Ma; Dilihumaier Duolikun; Qiaoling Yao (Archives of Endocrinology and Metabolism)
ABSTRACT Objective: A high-fat diet (HFD) significantly contributes to obesity and alters the neurological function of the brain. This study explored the influence of hypoxia-inducible factor (HIF-1) and its downstream molecules on obesity progression in the context of HFD-induced hypothalamic inflammation. Materials and methods: Utilizing a bioinformatics approach alongside animal models, targets and pathways related to hypothalamic obesity were identified via network analysis, gene target identification, gene ontology analysis, Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment, and subsequent validation in animal models. Results: HIF-1α has the potential to regulate the immune response by promoting immune infiltration and increasing the population of immune cells, particularly memory CD4 T cells, in the hypothalamus, primarily through its influence on ksr2 expression. Additionally, the analysis predicted five drugs capable of enhancing HIF-1-Ksr2 signalling. Conclusion: In conclusion, targeting Ksr2 with specific drugs represents a potential approach for addressing HFD-induced obesity. These novel findings lay the groundwork for developing dietary supplements and therapeutic interventions.